Push–pull thiophene-based small molecules with donor and acceptor units of varying strength for photovoltaic application: beyond P3HT and PCBM. Issue 34 (3rd August 2021) - Marinelli, Martina; Candini, Andrea; Monti, Filippo; Boschi, Alex; Zangoli, Mattia; Salatelli, Elisabetta; Pierini, Filippo; Lanzi, Massimiliano; Zanelli, Alberto; Gazzano, Massimo; Di Maria, Francesca
Abstract : Here is reported the synthesis of a family of thiophene-based heptamers alternating electron donor (D) and acceptor (A) units in a D–A′–D–A–D–A′–D sequence. Their multiple roles as active materials in BHJ solar cells are presented. Abstract : Here is reported an expedient synthesis implementing enabling technologies of a family of thiophene-based heptamers alternating electron donor (D) and acceptor (A) units in a D–A′–D–A–D–A′–D sequence. The nature of the peripheral A groups (benzothiadiazole vs. thienopyrrole-dione vs. thiophene- S, S -dioxide) and the strength of the donor units (alkyl vs. thioalkyl substituted thiophene ring) have been varied to finely tune the chemical-physical properties of the D–A oligomers, to affect the packing arrangement in the solid-state as well as to enhance the photovoltaic performances. The optoelectronic properties of all compounds have been studied by means of optical spectroscopy, electrochemistry, and density functional theory calculations. Electrochemical measurements and Kelvin probe force microscopy (KPFM) predicted a bifunctional behaviour for these oligomers, suggesting the possibility of using them as donor materials when blended with PCBM, and as acceptor materials when coupled with P3HT. Investigation of their photovoltaic properties confirmed this unusual characteristic, and it is shown that the performance can be tuned by the different substitution pattern. Furthermore, thanks to their ambivalent character, binary non-fullerene small-molecule organic solar cells with negligible values of HOMO and LUMO offsets were also fabricated, resulting in PCEs ranging between 2.54–3.96%.